Os gêneros literários nos jornais Almocreve de Petas e no novo Almocreve das Petas - Santos, Maria do Carmo dos (2017)
In the proposed work we aim to analyze the circulation of literary genres: epigram, maxim and play in the periodicals: O Almocreve de Petas (1798-1799) and Novo Almocreve das Petas (1871). In addition, we intend to demonstrate how the writer of Novo Almocreve das Petas (1871), Luiz de Araújo "appropriated" the writing and name of José Daniel Rodrigues da Costa to win the public reader’s attention of that time, who were not the literate ones, but from the lower classes of the Lisbon city. Regarding appropriation, we understand with Chartier (1991, p.180) that "it aims at a social history of uses and interpretations, referred to their fundamental determinations and inscribed in the specific practices that produce them." In order to reach the proposed objective, we resort the theoretical assumptions of authors that have dealt with the periodical press of the centuries that will be studied here, the concept of literature of the epoch, the historical context of Portugal and other questions concerning this research. Among others, we mention mainly the contributions of: Chartier (1991,1999), Pécora (2001), Barbosa (2007, 2010, 2012, 2015), Luca (2010) Eagleton (2006), Lajolo (2001), Martins (1987), Silva (1789) and Tinhorão (2004). Such studies will serve to support our analyzes that will be made to the corpus' research.